Rising beyond elastocapillarity. Issue 22 (14th April 2016) - Holmes, Douglas P.; Brun, P.-T.; Pandey, Anupam; Protière, Suzie
Abstract : We present the elastocapillary rise between swellable structures contacting a favorable solvent. The structures coalesce, curl, and exhibit fluid ratcheting. Abstract : We consider the elastocapillary rise between swellable structures using a favorable solvent. We characterize the dynamic deformations and resulting equilibrium configurations for various beams. Our analysis reveals the importance of the spacing between the two beams, and the elastocapillary length ec, which prescribes the relative magnitude of surface tension and bending stiffness in the system. In particular, we rationalize the transition between coalescence-dominated, bending-dominated, and swelling-dominated regimes, and enumerate the subtle interfacial mechanisms at play in the ratcheting of a fluid droplet trapped between the curling beams.